Relationships of the heteronchocleidids (heteronchocleidus, eutrianchoratus and trianchoratus) as inferred from ribosomal DNA nucleotide sequence data - Tan, W.B.; Fong, Mun Yik; Lim, L.H.S. (National University of Singapore, 2011)
The monogeneans, Heteronchocleidus, Eutrianchoratus and Trianchoratus, were postulated to be closely related based on their haptoral hard parts of three well-developed anchors and one vestigial anchor. In this present study, partial 28S rDNA sequences from 12 heteronchocleidids species (10 Trianchoratus spp. and two Eutrianchoratus spp.) were obtained. Phylogenetic trees generated based on 28S rDNA (from the present study and GenBank) using neighbour-joining (NJ), maximum parsimony (MP), maximum likelihood (ML) and Bayesian inference (BI) analyses show that members of these three genera constitute a clade. Within this main monophyletic clade are the Heteronchocleidus-Eutrianchoratus and the Trianchoratus clades. This suggests that the ancestral form of these monogeneans (probably with three developed and one vestigial anchor and two connective bars) diverged into two lineages, the Heteronchocleidus-Eutrianchoratus clade with the retention of bars and the Trianchoratus clade with the complete loss of connective bars. The Heteronchocleidus-Eutrianchoratus lineage diverged into the Eutrianchoratus group with the loss of one bar and the Heteronchocleidus group with the retention of the two bars. These monogeneans were initially assigned to the Heteronchocleidinae Price, 1968 which is herein raised to family status, Heteronchocleididae. The anabantoids and channids, which are the fi sh hosts of heteronchocleidids, are also shown to be closely related based on the phylogenetic tree generated on their partial Cytochrome b sequences obtained from GenBank. The monophyly of the heteronchocleidids, their distribution patterns on the anabantoid and channid hosts and the relatedness of their fi sh hosts suggest that the ancestral heteronchocleidids could be present on the ancestral forms of the anabantoids and channids. The hosts could have acquired their heteronchocleidids through inheritance and/or host transfers. Whatever the method of acquisitions, the process of speciation and extinction of some of the heteronchocleidid monogeneans on the different anabantoid and channid hosts gave rise to the present-day distribution patterns of the heteronchocleidids. Although the monophyly of the heteronchocleidids has been established, the interrelationships of this clade to the other monogenean groups and their evolutionary history need further investigation.